“Brain Drain” and the Global Mobility of High-Skilled Talent - Leipziger, Danny M. (World Bank, Washington, DC, 2012)
This note outlines the challenges of retaining and attracting high-skilled professionals, briefly assesses both the 'brain gain' and the 'brain drain' in the health sector, and examines some of the existing programs that encourage return. It provides an overview of the role of the diaspora in fostering the transfer of knowledge, technology, capital, and remittances.